Study of microRNA in diabetic nephropathy: Isolation, quantification and biological function. (March 2015) - Kantharidis, Phillip; Hagiwara, Shinji; Brennan, Eoin; McClelland, Aaron D.
Abstract In recent years, several studies have reported dysregulation of microRNA expression in disease with a growing interest focussed on targeting microRNAs as a novel therapy for human disease. This is especially true in diabetic nephropathy where the expression of several microRNAs is dysregulated, contributing to the increased expression and accumulation of extracellular matrix proteins and increased pro‐fibrotic signalling, ultimately resulting in renal fibrosis. The development of various techniques and microRNA reagents has enabled work to progress very rapidly in this area. In the present article, the authors describe the methods they have used that have enabled them to contribute to our current understanding of the role of microRNAs in diabetic nephropathy.